Hints for a reinterpretation of the special detention regime in light of the principle of proportionality (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
More than 30 years after the introduction of 41 bis, there is a need to thoroughly rethink its role and discipline. While convinced of the legitimacy of the purpose that this measure pursues and of its persistent usefulness, it is believed that a reinterpretation of the discipline in light of the principle of proportionality may provide important food for thought with a view to its refounding in the perspective of a reasonable balance between special prevention needs and the protection of fundamental rights.
Keywords: 41 bis; proportionality principle; balancing; organized crime; human rights